2012
DOI: 10.3324/haematol.2012.074534
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide, melphalan, and prednisone, followed by lenalidomide maintenance, improves health-related quality of life in newly diagnosed multiple myeloma patients aged 65 years or older: results of a randomized phase III trial

Abstract: The MM-015 trial assessed the effect of lenalidomide-based therapy on health-related quality of life. Patients (n=459) with newly diagnosed multiple myeloma aged 65 years or over were randomized 1:1:1 to nine 4-week cycles of lenalidomide, melphalan, and prednisone, followed by lenalidomide maintenance; or lenalidomide, melphalan, and prednisone, or melphalan and prednisone, with no maintenance therapy. Patients completed health-related quality of life questionnaires at baseline, after every third treatment cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 23 publications
9
62
0
Order By: Relevance
“…Furthermore, during the MM-015 phase III trial, with a median follow up of 30 months, more patients treated with MPR-R achieved minimal important improvements in HRQoL outcomes compared with those on MP, and there were no significant differences in HRQoL outcomes between patients on continuous treatment versus placebo. 39,43 Although not all the statistically significant changes reached the MID threshold, Rd showed evidence of clinically meaningful improvement in Pain and in HRQoL as measured by EQ-5D, whereas MPT failed to demonstrate a clinically meaningful improvement in any domain (with the exception of 1 time point in EQ-5D). Neither treatment showed a clinically significant worsening of HRQoL in any domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, during the MM-015 phase III trial, with a median follow up of 30 months, more patients treated with MPR-R achieved minimal important improvements in HRQoL outcomes compared with those on MP, and there were no significant differences in HRQoL outcomes between patients on continuous treatment versus placebo. 39,43 Although not all the statistically significant changes reached the MID threshold, Rd showed evidence of clinically meaningful improvement in Pain and in HRQoL as measured by EQ-5D, whereas MPT failed to demonstrate a clinically meaningful improvement in any domain (with the exception of 1 time point in EQ-5D). Neither treatment showed a clinically significant worsening of HRQoL in any domain.…”
Section: Discussionmentioning
confidence: 99%
“…42 The observed differences in HRQoL between continuous Rd and MPT likely reflect both the good tolerability of the Rd regimen (leading to fewer side effects of treatment) and prolonged time to progression with continuous Rd. Improvements in HRQoL have previously been reported during treatment with melphalan, prednisone, lenalidomide followed by lenalidomide maintenance (MPR-R) in patients with NDMM, 39,43 and the addition of thalidomide to MP did not negatively affect HRQoL. 44 However, our results contrast with the HRQoL trade-off reported with bortezomib in the VISTA trial, which compared MPV versus MP in NDMM patients and in which MPV had superior PFS and OS efficacy, but where patients' HRQoL was significantly compromised, especially in the first four cycles of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of PRO data that is captured does not make it onto the regulatory approved label, this is particularly noted in oncology [4] which is currently being actively addressed by industry and regulators [5]. PRO data, particularly HRQL data, provides essential contextualizing information in oncology so that the quality of improved survival can be understood from patient's perspective [6,7]. PROs also provide important supporting evidence of treatment benefit that are of value to other stakeholders.…”
mentioning
confidence: 99%
“…[8][9][10][11] In the current issue of the Journal, three interesting papers have been published evaluating the role of lenalidomide alone or in combination with steroids and alkylating agents in three different settings of patients with plasma cell dyscrasia. [12][13][14] Coman et al presented the results of a retrospective multicenter study on MM patients receiving lenalidomide alone or in combination with dexamethasone as salvage therapy after allo-SCT. 12 This study is the largest reported in this setting.…”
mentioning
confidence: 99%